Communication Models and Intervention Strategies for Children with Multiple Barriers: Literature Review - Atika Nurul Azizah; Endah Agustine Wulandari; Muria Jayanti Azzahra; Salwa Alhuda; Jasmine Meilika Zahra; Citra Ashri Maulidina (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
Children with multiple disabilities often experience communication difficulties due to a combination of sensory, physical, and cognitive barriers that affect their ability to interact socially. This article examines communication intervention models and strategies for children with multiple barriers through a literature review. The study was conducted on 20 scientific articles published over the last five years, obtained from various relevant sources. Then analyzed using content analysis. The results of the study show that effective communication interventions include direct communication approaches grounded in empathy, the development of intervention models through research and development (R&D) methods, and the use of Augmentative and Alternative Communication (AAC). Social environmental support, the roles of teachers and families, and adapting interventions to the child's individual characteristics are important factors in successful communication. Therefore, communication interventions need to be designed adaptively and holistically to support communication development and quality of life for children with multiple barriers.